C-Telopeptide in Relation with Osteoporosis Risk Classification Using Osteoporosis Self Assessment Tools for Asian (OSTA) in Postmenopausal Women - Willy Pangestu; Maria Loho; Freddy Wagey (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To determine the correlation between Câ€telopeptide with osteoporosis risk by using Osteoporosis Self Assessment Tools for Asian (OSTA) in postmenopausal women. Method: An analytic crossâ€sectional study of 31 postmenopausal women in Prof. Dr. RD Kandou Hospital, Manado. Samples were collected through consecutive sampling. Data was analyzed using Pearson test with significance level of p>0.05. Result: Our sample consisted of 31 postmenopausal women. Mean OSTA score is â€1.02K2.54. Sixteen women (51.61%) were deemed to have low risk, 8 women (25.81%) deemed to have moderate risk and 7 women (22.58%) deemed high risk based on the OSTA score. The mean Câ€telopeptide plasma level of our sample is 0.52K0.25 ô€g/l. We found plasma Câ€telopeptide level and OSTA score were normally distributed. Correlation analysis using Pearson test identified a significant negative correlation between plasma Câ€telopeptide level and OSTA score (r=â€0.768; p=0.001). Conclusion: There is a significant negative correlation between plasma Câ€telopeptide level with risk of osteoporosis based on OSTA score in postmenopausal women. Keywords: OSTA score, plasma Câ€telopeptide, postmenopausal women